(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Organizing rhythmic gymnastics classes for preschool children requires consideration of their psychophysiological development, which is characterized by the leading role of play, the need for constant emotional reinforcement, and the predominance of figurative thinking. The formation of stable motivation at this stage is possible through the integration of physical exercises with role-playing and narrative elements, which ensure engagement and foster a positive attitude toward training. This paper presents the results of a pedagogical experiment aimed at testing the effectiveness of the author’s method Author’s Warm-up Method "Sports Track" for Children 4–6 Years in Rhythmic Gymnastics, designed with a play-based framework and the gradual development of basic physical qualities. The experiment involved two groups of children aged 4–6 years (12 participants in each), which allowed for a comparison between the traditional training program and the “Sports Track” method. The study assessed attendance, motivational involvement, emotional state, and the outcomes of basic motor tests. The results revealed that in the experimental group attendance increased from 82 % to 95 % (compared to 83–86 % in the control group), the average emotional state score rose from 3.4 to 4.6 points, and motor performance indicators (balance, flexibility, rhythm) improved by 40–50 %, whereas in the control group the growth ranged only from 9 % to 14 %. Qualitative analysis confirmed higher independence, more active participation in narrative-play exercises, improved group interaction, and the development of intrinsic interest in training. According to parents’ feedback, children were more eager to attend classes, demonstrated exercises at home, and expressed positive emotions about gymnastics. Thus, the proposed method has proven its effectiveness as a tool for building stable motivation and improving the quality of initial sports training among preschool children.